2018
DOI: 10.1002/celc.201800230
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen‐Doped Hierarchical Porous Carbon through One‐Step Activation of Bean Curd for High‐Performance Supercapacitor Electrode

Abstract: New nitrogen‐doped hierarchical porous carbons (HPCs) with large surface areas were prepared from bean curd through a one‐step impregnation activation method at 750 °C with CH3COOK as an activating agent. The porous carbons were characterized by a variety of techniques such as N2‐sorption analysis, scanning electron microscope (SEM), transmission electron microscope (TEM), and X‐ray photoelectron spectroscopy. The results show that there are numerous macropores with a pore size of ∼200 nm observed by SEM and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 54 publications
0
21
0
Order By: Relevance
“…The mung bean carbons with different structures and compositions offer a chance for investigating the structure‐performance relationship of bio‐carbon as supercapacitor. Based on other works, two points are beneficial to the specific capacitance of carbon material: (1) hierarchical nanostructure composed of macroporous and meso/microporous, which facilitates fast mass transport, along with large surface area for electrical charge storage; (2) heteroatom doping generate extra pseudocapacitance As shown in Figure , the specific capacitance was calculated by GCD curves and correlated with BET surface area, N content, charge transfer resistance Rct, and defect degree I D /I G . The results indicate that the specific capacitance correlates positively to the BET surface area, N content, and I D /I G .…”
Section: Resultsmentioning
confidence: 99%
“…The mung bean carbons with different structures and compositions offer a chance for investigating the structure‐performance relationship of bio‐carbon as supercapacitor. Based on other works, two points are beneficial to the specific capacitance of carbon material: (1) hierarchical nanostructure composed of macroporous and meso/microporous, which facilitates fast mass transport, along with large surface area for electrical charge storage; (2) heteroatom doping generate extra pseudocapacitance As shown in Figure , the specific capacitance was calculated by GCD curves and correlated with BET surface area, N content, charge transfer resistance Rct, and defect degree I D /I G . The results indicate that the specific capacitance correlates positively to the BET surface area, N content, and I D /I G .…”
Section: Resultsmentioning
confidence: 99%
“…HPC‐10 clearly has the lowest R ct among the four HPCs samples in both 1 M H 2 SO 4 and 6 M KOH (Table S2), which correlates with its highest specific capacitance and performance retention. Note that R ct of HPC‐10 in 6 M KOH is actually lower slightly than that in 1 M H 2 SO 4 (Table S2), which can be understood in terms of the easier diffusion for electrolyte (K + and OH − ) ions in carbon framework in KOH case . Fast charge transfer process in HPC‐10 likely comes from two main contributors, i. e., the presence of hierarchical porous framework containing balanced amount of micropores, mesopores, and macropores and the presence of N and O dopants in optimum amount .…”
Section: Resultsmentioning
confidence: 91%
“…This is most likely because the ions in KOH (K + : 3.31 Å, OH − : 3.00 Å) aqueous solution are larger than those in H 2 SO 4 (H + : 2.82 Å, SO 4 2− : 3.79 Å) aqueous solution. Thus, the former exhibit lower diffusion rate to leave/reach micropores; resulting into lower surface utilization …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As sustainable and renewable biomass materials, legumes and byproducts of legumes are rich in plant proteins, 31 which is mainly composed of complete protein with elements of C, S, O and N. Hence, legumes-derived HPCs have been extensively applied as highly conductive materials for supercapacitor. 11,[32][33][34][35][36] For instance, Yao et al 11 reported Bradyrhizobium japonicumderived 3D hierarchical porous carbon with high N content, the as-prepared material was of large S BET , unique threedimensional hierarchical porosity and also excellent electrochemical performance. Lin et al 33 synthesized nitrogen-doped HPCs by using soybean as starting material, and a high energy density was obtained.…”
Section: Introductionmentioning
confidence: 99%